Analysis Of Complication Treatment Design In Hepatitis B Patients In The Outpatient Facility Of Dr. Moewari Hospital, Surakarta - Afnisyah Nurcahyati; Kharisma Jayak Pratama; Niken Luthfiyanti (International Journal of Health Engineering and Technology, 2026)
Hepatitis is an inflammation of the liver that is generally caused by a viral infection. There are five hepatitis viruses, namely Hepatitis A Virus (HAV), Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), Hepatitis D Virus (HDV) and Hepatitis E Virus (HEV). Hepatitis B is a liver disease caused by the hepatitis B virus (HBV). HBV can cause acute or chronic liver inflammation, in a small number of cases it can progress to liver cirrhosis or liver cancer (Andriani et al., 2020). This study aims to determine the patient profile and use of hepatitis B drugs and evaluate Hepatitis B treatment in patients at the Outpatient Installation of Dr. Moewardi Regional Hospital using a non-experimental descriptive observational method with retrospective quantitative data collection. The results of the study showed that of the 99 hepatitis B patients, the majority were male (67.68%) and aged >55 years (46.5%). Most patients received antiviral therapy (60.61%), with tenofovir being the most commonly used drug (78.78%), followed by entecavir (17.17%). Evaluation of treatment suitability showed that all doses and frequencies of antiviral and hepatoprotective therapy administered were in accordance with national guidelines and MIMS references (100% compliance). Curcuma was the most frequently used hepatoprotective agent (64.64%). This indicates that the use of hepatitis B medications at Dr. Moewardi Regional Hospital is in accordance with applicable therapy standards. Based on a study of 99 hepatitis B patients, most patients received antiviral and supportive therapy according to guidelines. The use of medications, both antiviral and hepatoprotective, was appropriate in type, dose, and frequency. Patient management demonstrated rational and clinically appropriate therapy.